Physiotherapy in Bangladesh: Inequality Begets Inequality - Mamin, Firoz Ahmed; Hayes, Rieke (Frontiers in Public Health, 2018)
Background: The demand for health services in developing countries often outweighs provision. This article describes the present condition of physiotherapy in Bangladesh. Physiotherapy is not recognised as a profession by the government. There is no single registration and regulation body. The health-related and economic benefits of physiotherapy are not felt by the majority of Bangladeshi citizens. Areas covered: The burden of disease is changing and Bangladesh needs a profession that specializes in physical rehabilitation to face these challenges. This article outlines the benefits to patients and the wider economy from a broadly-based physiotherapy regime for all Bangladeshi citizens. It describes the many barriers the profession faces. Conclusion: Physiotherapy is efficacious in many post-trauma situations and long-term conditions. Economic evidence supports the provision physiotherapy as a cost-effective treatment which should be considered as part of the provision of a universal health care service. Official recognition of the protected ‘physiotherapist’ title and a single registration and regulation agency are recommended.